Determination of Gold Mineralization Trends and Patterns in the Kibi Gold Zone, Ghana - Dwumfuor, M. K. (University of Ghana, 2023)
Kibi gold deposit shares similarities with several known gold deposits in Ghana, however, it has not attracted the desired attention from researchers and explorers. Most of the available data and reports produced by these explorers are not well documented. This study sought to unravel the gold mineralization trends of the ill–defined Kibi gold zone at the northern part of the Kibi-Winneba belt in Ghana using litho-structural mapping, geophysical, petrographical and geochemical datasets for effective exploration and exploitation designs. Airborne magnetic, ground resistivity and induced polarization datasets were processed to interpret the geology and estimate the depth to basement of magnetic source in the area. . Thin and polished section petrographic assessment of modal and ore minerals respectively were determined on representative samples. Major and trace element composition of selected representative rock samples were determined by X-ray fluorescence (XRF) and gold contents were determined by fire assay-atomic absorption spectrometry (FA-AAS). The Kibi gold district is underlain by deformed and altered schist, sodic greywacke, andesitic tuff (volcaniclastic rock) and basaltic to alkali basalt which is faulted to form hanging and footwall mafic volcanic rocks. The majorgeological structures observed in the area are lineation, foliations, folds, fractures/joints, faults, shear zones and quartz veins. These structures represent at least three major deformation events, namely D1, D2 and D3. D1 compressional deformation resulted in NNW-SSE oriented sub-horizontal foliations and stretching lineation, as well as E-W trending tight-isoclinal recumbent folds. The D2 compressional event created regionally and locally oriented dextral shear zones trending NE-SW, as well as NE-SW trending asymmetric to upright open folds. Gold mineralization is associated with D2 structures. The linear features in the area generally trend NW-SE, E-W and NE-SW and are occasionally dissected in several sections by NW-SE (T1) and NE-SW (T2) mafic dykes and north-south fractures (F1). D3 represents splays of D2. Hydrothermal alteration along quartz-carbonate veins varies greatly, typified by strong silicification, sulphidization, carbonatization, albitization, and sericitization. This is also linked to dispersed pyrrhotite, pyrite, and arsenopyrite (+/- sphalerite) as well as patchy to ubiquitous sulphidization. Gold mineralization is both hosted as quartz-bearing veins and disseminations in the metasedimentary rocks with quartz veins or as disseminated in wall rocks without quartz veins. The mineralization is characterized by ore mineral assemblage which consists of pyrite, chalcopyrite, magnetite in veins; magnetite, tourmaline and micron-sized sulphides in metasedimentary rocks. Pyrite is the main pathfinder mineral for gold even though chalcopyrite, sphalerite, rutile, haematite, magnetite, pyrrhotite and molybdenite are good indicators. Gold is associated with 2nd generation pyrite which is fractured and has sieve texture. The main pathfinder elements for gold in the Kibi area are Ag and As. Alteration styles in the area include albitization, carbonatization, sericitization, silicification and sulphidization. The andesitic tuff samples are peraluminous and tholeiitic and the occurrence of calc-alkaline basalt and ocean-floor basalt indicate possible subduction-related magmatism in a volcanic arc environment. Detritus of the sodic greywackes are mafic to intermediate composition and derived from an oceanic island arc provenace. Basaltic to alkali basalts are predominantly metaluminous and derived from volcanic arc-related lavas. The calc-alkaline nature of the hanging wall suggests subsequent metasomatism that resulted in the emplacement of gold. The arc-related signatures suggest a compressive domain, which can be attributed to orogenic events that might have created pathways for the emplacement of the gold. The composition of host rocks, alteration patterns, structural control and ore paragenesis suggested an orogenic metamorphic (transitional mesothermal-epithermal) gold-type mineralization in the Kibi Gold Zone.
PhD. Earth Science
Keywords: gold deposits; Ghana; Kibi-Winneba